Pengembangan Bahan Ajar Strategi Pembelajaran Fisika Berbasis Generative Artificial Intelligence untuk Meningkatkan Kemampuan Merancang Pembelajaran Calon Guru Fisika - Desy Sari Ayunda; Nurmala Sari; Muhammad Muhammad; Novi Sari Liani (Social Science Academic, 2026)
The development of Generative Artificial Intelligence (GenAI) provides new opportunities in the development of learning in higher education, including in the preparation of teaching materials that support the pedagogic competence of prospective teachers. However, the teaching materials in the Physics Learning Strategy Course are still dominated by the presentation of theory and have not integrated the systematic use of GenAI in the learning design process. This research aims to develop valid, practical, and effective teaching materials for GenAI-based Physics Learning Strategies to improve the ability to design learning for prospective physics teachers. The research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research subjects amounted to 34 students of the Physics Education Study Program, Faculty of Teacher Training and Education, Malikussaleh University. Data collection is carried out through expert validation sheets, student response questionnaires, rubrics on learning design ability assessments, observations, and documentation. Data were analyzed using descriptive analysis of percentage, Normalized Gain (N-Gain), and effect size (Cohen's d). The results of the study showed that the teaching materials obtained a very good category based on the validation of media experts (84.57%–91.12%), material experts (86.18%–94.26%), and linguists (89.36%–93.21%). The results of the practicality test also showed a very practical category with a percentage of 89.15% in individual tests, 91.42% in small group tests, and 94.08% in field tests. The effectiveness of teaching materials was shown by the improvement of the ability to design learning with an N-Gain value of 0.79 and learning strategy competence of 0.76 which was in the high category, and effect size (Cohen's d) of 1.48 and 1.36 respectively which showed a very large effect. Thus, the GenAI-based teaching materials developed meet the criteria of valid, practical, and effective so that they are suitable for use as a learning resource in the Physics Learning Strategy Course.